2021
DOI: 10.2478/rtuect-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Ni Underlayer Effect for the Structure Development and Visible Light Photocatalytic Efficiency of Carbon-Doped TiO2 Film

Abstract: Photocatalytic treatment of contaminated aqueous solutions makes use of the specific interaction between photocatalysts and ultra-violet or visible light irradiation. This method belongs to the wider class of Advanced Oxidation Processes that generates reactive oxygen species (peroxides, superoxide, hydroxyl radical, singlet oxygen, etc.) and uses them for the non-selective oxidation of various organic and inorganic compounds. In THE current study magnetron sputtering technique was used to deposit carbon-doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Part of HDPE beads was precovered by a thin nickel underlayer to test if it improves the photocatalytic activity in the case of ZnO. Our previous studies [28,44] showed that the metallic underlayer can positively affect photocatalytic performance under both UV-B and visible light irradiation. Additionally, some studies suggest that the recombination rate of electron-hole can be reduced and photocatalytic efficiency improved using metallic substrates and transition metals dopants [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Part of HDPE beads was precovered by a thin nickel underlayer to test if it improves the photocatalytic activity in the case of ZnO. Our previous studies [28,44] showed that the metallic underlayer can positively affect photocatalytic performance under both UV-B and visible light irradiation. Additionally, some studies suggest that the recombination rate of electron-hole can be reduced and photocatalytic efficiency improved using metallic substrates and transition metals dopants [45][46][47].…”
Section: Introductionmentioning
confidence: 99%